BRICs Nations Growing Impact on the Global Health Sector - M. B. Jakovljevic; N. V. Ekkert; M. S. Mikerova; V. A. Reshetnikov (Vestnik MGIMO-Universiteta, 2019)
The most notable feature of the past five centuries of global economic history dating back from Colonial Age until the present accelerated globalization is the persistence of «North–South» division between the global rich and poor. This ground pattern has been falling apart over the last three decades with the rise of BRICs emerging economies (Brazil, Russia, India, China). The Chinese Belt and Road Initiative fosters further rapid growth and synergy among these large nations. This ambitious and historically unprecedented infrastructural project if successful can lead to a formation by 2049 of a huge common economic zone bringing opportunities for multilateral development to the BRICs. These profound changes have deep implications for the global health care sector. Previous research on health and pharmaceutical spending has clearly documented that low- and middle-income economies (LMICs), led by these emerging markets, have doubled their share in global health spending from roughly 20% up to approximately 40% in purchasing power parity terms. Alongside with these global developments, a decade ago, some of the leading Western academic centers, confirm new era of rising world’s geo-economic and geopolitical multipolarity. The world witnesses this process being accelerated today and seek deeper understanding how it will reflect on long term health and pharmaceutical expenditure trends, particularly in the leading BRICs emerging markets being a front runner of such evolution.The authors declare absence of conflict of interests.